Developing an Empowerment Model for University Students' Skills in the Cultivation of Pumpkin Plants - Evy Ratna Kartika Waty; Rani Mega Putri; Dian Sri Andriani; Shomedran Shomedran; Yanti Karmila Nengsih (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study aimed to develop an empowerment model for students’ skills in cultivating pumpkin plants, especially for community education at the Faculty of Teacher Training and Education at University in Palembang. The type of research used was modified with four stages based on the ADDIE process: analyze, design, develop, and implement. The research subjects were Community Education Faculty of Teacher Training and Education students and two validators. The researchers conducted a group test with 26 students. Through this test, researchers can discover the weaknesses and shortcomings of the empowerment model based on how students assess the design, scope of material and techniques used. The data were collected using questionnaires. The results showed that at the stage of needs analysis through the distribution of online questionnaires, it was found that students needed this empowerment model to support various activities in the Education Park. Furthermore, the planning stage, which produces a storyboard as the initial design of the product, and the results from the validation test stage for development by validator experts make a total score of 111 with an average percentage of 92.45% and excellent feasibility. These results indicate that the product can be applied at the Education Park Faculty of Teacher Training and Education Students at Sriwijaya University. The next stage is implementation, with the results of product trials in small groups resulting in a total score of 1196 with a percentage of 92%, which indicates that the product is feasible to be applied.